Improving Students' Understanding of Islamic Education Learning by Using the Inquiry Learning Model at SMA Negeri 1 Darul Imarah - Hidayatullah (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to find out whether the application of the inquiry model can improve the economic learning outcomes of students in class X E-1 of SMA Negeri 1 Darul Imarah. This research method uses two cycles. The research subjects consisted of 36 students in class X E-1 of SMA Negeri 1 Darul Imarah for the 2022/2023 academic year, with details of 17 male students and 19 female students. The research was conducted in two cycles, and each cycle consisted of two meetings. The data was analyzed using a comparative descriptive technique, which compared the initial condition with the results obtained in each cycle. In addition, qualitative descriptive analysis based on the results of observation and reflection in cycle I and cycle II was also used. Through the application of the inquiry model in economics subjects, especially material on the role of the market in the economy, it is hoped that it can improve students' understanding and learning outcomes. In cycle I, it is known that there is a significant increase compared to the initial condition. If in the initial condition only 15 students achieved the Minimum Completeness Criteria (KKM) with a score of 70, then in the first cycle the number increased to 21 students. At the end of cycle II, the number of students who met the KKM increased again to 23 people. Thus, most of the students of class X E-1 of SMA Negeri 1 Darul Imarah showed an increase in learning outcomes in the material on the role of the market in the economy. In percentage terms, the level of student learning completeness increased from 41.47% in the initial condition to 63.89% in the first cycle, and reached 94.44% in the second cycle. Based on these results, it can be concluded that the application of the inquiry model is able to improve the economic learning outcomes of students in class X E-1 of SMA Negeri 1 Darul Imarah, especially in the material on the role of the market in the economy.